Applicability of optimality theory in selected religious texts from the Holy Quran - Al-Juborry, Fadhil Athab (Opción, 2019)
This study is intended to shed light on the applicability of optimality theory in Quran verses, particularly with respect to Arabic syllable structure via comparative qualitative research methods. As a result, the occurrence of geminates is justified by the IDENT-IO constraint that recommends that input representation of an input that is geminate should appear in the output. In conclusion, Semisyllable branching is the most optimal candidate Standard Arabic appeal because it contributes substantially to resolving both coda and onset clusters resulting in more natural utterances